AGRO-BIODIVERSITY CONSERVATION THROUGH SEED BANKING: A CASE STUDY FROM MID-WESTERN AND FAR-WESTERN NEPAL - Pokhrel, Chandra P.; Bhandari, Vimla; Lakhe, Pramesh; Yadav, Ram Kailash P. (Ecoprint: An International Journal of Ecology, 2014)
The present paper deals with the perception and practices of farmers on production, processing and storage of seeds as well as role of Community Seed Banks (CSBs) in seed supply and conservation of agro-biodiversity. The study was conducted in three VDCs namely Belwa, Masuriya and Beldandi of Bardia, Kailai and Kanchanpur districts, respectively. Of the sampled respondents, 44.4% used only local varieties and the rest of them used all local, improved and hybrid varieties. Farmers in the study area have their own criteria of seed selection such as yield potential, growth period, resistance to disease and pest, taste, shape and color. Traditionally, farmers store their seeds in a special clay pot called “Dehari” and “Kuthali: CSB is the alternative way of their seed storage. Total 75 varieties of paddy, 13 varieties of wheat and 10 varieties of maize were stored in CSBs. Eight varieties of millet, 5 varities of mustard and 12 varieties of pulse, 4 varieties of gram and two varieties of soybean were also stored. CSBs were found to be useful to the farmers in many ways such as easy availability of seeds, on-farm conservation of local varieties, conservation of local and traditional knowledge and change in their livelihoods. DOI: http://dx.doi.org/10.3126/eco.v19i0.9852 Ecoprint An International Journal of Ecology Vol. 19, 2012 Page: 1-5 Uploaded date: 2/14/2014